Signaling From Lysosomes Enhances Mitochondria-Mediated Photodynamic Therapy In Cancer Cells - Quiogue, Geraldine (2009)
In photodynamic therapy (PDT), visible light activates a photosensitizing drug added to a tissue, resulting in singlet oxygen formation and cell death. Assessed by confocal microscopy, the photosensitizer phthalocyanine 4 (Pc 4) localizes primarily to mitochondrial membranes in cancer cells, resulting in mitochondria-mediated cell death. A Pc 4 derivative, Pc 181, accumulates into lysosomes. In comparison to Pc 4, Pc 181 was a more effective photosensitizer promoting killing cancer cells after PDT. The mode of cell death after Pc 181-PDT is predominantly apoptosis, and pancaspase and caspase-3 inhibitors prevent onset of the cell death. To assess further how lysosomes contribute to PDT, we monitored cell killing of A431cells after PDT in the presence and absence of bafilomycin, an inhibitor of the acidic vacuolar proton pump that collapses the pH gradient of the lysosomal/endosomal compartment. Bafilomycin by itself did not induce toxicity but greatly enhanced Pc 4-PDT-induced cell killing. In comparison to Pc 4, less enhancement of cell killing by bafilomycin occurred after Pc 181-PDT at photosensitizer doses producing equivalent cell killing in the absence of bafilomycin. These results indicate that lysosomal disruption can augment PDT with Pc 4, which targets predominantly mitochondria, but less so after PDT with Pc 181, since Pc 181 already targets lysosomes.